Analysis Of The Implementation Of The Foster Parents Movement To Prevent Stunting (GENTING) Program In East Seram District, 2025–2026 - Suhartini Suhartini; Dian Novita Maba; M. Yunus (CV. AFDIFAL MAJU BERKAH, 2026)
Stunting remains a serious nutritional challenge in Seram Bagian Timur (SBT) District, with a prevalence of 27.5% in 2023 — well above the national average. In response, the Gerakan Orang Tua Asuh Cegah Stunting (GENTING) program was socialized in SBT in January 2025, targeting 218 at-risk families across 15 sub-districts. This study aims to analyze the early implementation of the GENTING program in SBT District in 2025-2026 using an Input-Process-Output (IPO) framework. A descriptive quantitative approach was applied using secondary data, comprising the 2024 stunting-risk family recapitulation, field verification and validation (verval) results, and Orang Tua Asuh (OTA) distribution records as of June 9, 2026. Three key findings emerged: first, there were significant inconsistencies between planned targets and verval results across sub-districts, with deviations ranging from -75% to +460% of initial targets; second, OTA assistance coverage reached only 9.0% of 211 verified beneficiaries, with 7 sub-districts receiving no assistance at all; third, 95% of distributed aid consisted of nutritional support despite 24.6% of target families lacking adequate sanitation facilities, alongside inconsistencies in aid values, some falling below the national minimum standard of IDR 15,000 per day. It is concluded that the early implementation of GENTING in SBT faces three structural problems: data accuracy in planning, geographic disparity in aid distribution, and suboptimal matching of aid type to beneficiary risk profiles.